2018
DOI: 10.1136/oemed-2017-104571
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence due to different musculoskeletal diagnoses by occupational class: a register-based study among 1.2 million Finnish employees

Abstract: ObjectivesThose in lower occupational classes have an increased risk of sickness absence due to musculoskeletal diseases (MSDs), but studies examining the associations simultaneously across specified diagnostic groups within MSDs are lacking. We examined occupational class differences in the occurrence and length of long-term sickness absence due to different musculoskeletal diagnoses.MethodsA 70% random sample of employed Finns aged 25–64 years old at the end of 2013 was linked to data on sickness absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
3
30
1
2
Order By: Relevance
“…Impaired work ability and reduced well-being due to long-term musculoskeletal pain (MSP) in the neck, shoulder and back are considered occupational health problems that can result in workers taking sick leave (SL) [1][2][3][4]. Long-term SL, in particular, constitutes a major economic burden for society [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired work ability and reduced well-being due to long-term musculoskeletal pain (MSP) in the neck, shoulder and back are considered occupational health problems that can result in workers taking sick leave (SL) [1][2][3][4]. Long-term SL, in particular, constitutes a major economic burden for society [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the prevalence and incidence of SL due to long-term MSP (≥ 3 months) is high among women [2,7]. According to a recent report from the Swedish Social Insurance Agency (SIA), 61%…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising that individuals with ankle symptoms reported higher work limitations than the controls; as 67% of the symptomatic reported moderate to considerable work limitations compared to 1.9% of the control (see chapter 8). The negative impact of chronic pain on work participation has been reported in the literature 432,433 . The symptomatic group also reported higher levels of depression, lower function and were 9% more likely to present with clinical catastrophizing than controls.…”
Section: Summary Of Thesis Findings In Relation To the Objectivesmentioning
confidence: 98%
“…Chronic pain has also been reported to negatively impact on work performance 432 and attendance 433 . A Finnish study of 1.2 million employees identified that musculoskeletal conditions (OA, disc disorders and rheumatoid arthritis) were associated with long episodes of sick leave 433 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation